AMC MALANG - SETENGAH ABAD DALAM PERAN DAN AKTIVITAS BERKEGIATAN DI ALAM TERBUKA - Samudro, Odok (Sejarah dan Budaya: Jurnal Sejarah, Budaya, dan Pengajarannya, 2021)
AMC Malang, founded on December 26, 1969, is an old community group of mountain climbers, still existing and having a reputation. In the age of half a century AMC continues to play a role and its outdoor activities. In 1971, AMC together with TMS-7 in BK-PG Malang held the second national exercise for nature lovers. In 1973, AMC together with 11 other groups formed the association of MAHAMERU Malang and a member became the vice chairman of the board. In 1975-1980, AMC joint to improve the expertise of its members in the parachuting training for the Para-Rescue SAR Malang coordinated by MAPAC. An AMC member was enrolled in the Parachuting Training Course of Brimob-Police in Depok, then became a MAPAC trainer and a skilled parachutiest of BPC. In 1976-1984, AMC played a role in pioneering soft-ball in Malang, winning the second Division of Perbasasi East Java. In 1985-2005 AMC activity inactive, in 2005-2019 AMC revived, consolidated and revitalized the organization. Develop pioneering activities in the core competences of nature lovers, cooperation and social-community service based on science and technology in the fields of geoscience, disaster mitigation, Navcom and education and training are very beneficial for the social community. AMC Malang didirikan 26 Desember 1969 adalah komunitas tua pendaki gunung, masih eksis dan mempunyai reputasi. Di  usia setengah abad AMC tetap berperan dan bergiat di alam terbuka. 1971, AMC bersama TMS-7 dalam BK-PG Malang menyelenggarakan Gladian Nasional 2 Pecinta Alam. 1973, AMC bersama 11 kelompok lain membentuk PPPA-MAHAMERU Malang dan seorang anggotanya menjadi wakil ketua pengurus. 1975-1980, AMC ikut meningkatkan keahlian anggotanya latihan terjun Para-Rescue SAR Malang-MAPAC. Seorang anggota AMC diikutkan pendidikan terjun di Brimob-Kepolisian Depok, menjadi pelatih MAPAC dan peterjun handal BPC. 1976-1984, AMC berperan mempelopori soft-ball di Malang, berprestasi juara Divisi 2 Perbasasi Jatim. 1985-2005 AMC non-aktif, 2005-2019 AMC bangkit, berkonsolidasi dan merevitalisasi organisasi. Mengembangkan kepeloporan core-kompetensi pecinta alam dan  pengabdian masyarakat berbasis IPTEK di geosain, mitigasi bencana dan diklat yang bermanfaat bagi masyarakat.